(untitled) (Medical Forum Monthly, 2020)
Objective: To determine the diagnostic precision of serum albumin as well as its correlation with the esophageal varices in different grades among patients of chronic liver disease. Study Design: Cross sectional study Place and Duration of Study: This study was conducted at the Department of Gastroenterology, Asian Institute of Medical Sciences (AIMS), Hyderabad. The study was carried out from February 2019 to July 2019. Materials and Methods: Patients of age 25-60 years of either gender presented in outpatient department with history of chronic liver disease were included. Blood samples were collected for the analysis of serum albumin level while Endoscopy was performed for the confirmation and grading of esophageal varices. All information was collected using pre-tested questionnaire. Results: Mean age of study participants was 49.87+12.58 years while majority 67.56% participants were male. Esophageal varices on serum albumin were found positive in 39 (41.1%) cases and EGD was found positive in 38.95% cases. The sensitivity of esophageal varices on serum albumin was 81.40%with specificity of 88.46%. The PPV value was 85.36%, NPV value was 85.18% and diagnostic accuracy of esophageal varices on serum albumin was 85.26%. A statistically significant correlation (p-value < 0.05) between serumalbumin level and esophageal varices in different grades among chronic liver disease patients was determined. Conclusion: Serum albumin is a useful prognosticator of esophageal varices among patients of chronic hepatic disorder.